2018
DOI: 10.1080/00480169.2018.1426504
|View full text |Cite
|
Sign up to set email alerts
|

Plasma dispositions and concentrations of ivermectin in eggs following treatment of laying hens

Abstract: The low plasma bioavailability of IVM observed after oral administration in laying hens could result in lower efficacy or subtherapeutic plasma concentrations, which may promote the development of parasitic drug resistance. Due to high IVM residues in eggs compared to the maximum residue limits for other food-producing animal species, a withdrawal period should be necessary for eggs after IVM treatment in laying hens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…The same dose of ivermectin (0.2 mg/kg) was administered to six birds via oral gavage using a needleless syringe. The dose of 0.2 mg/kg was based on Cirak et al [ 25 ]. The remaining four chickens were assigned to a control group that received a water gavage.…”
Section: Methodsmentioning
confidence: 99%
“…The same dose of ivermectin (0.2 mg/kg) was administered to six birds via oral gavage using a needleless syringe. The dose of 0.2 mg/kg was based on Cirak et al [ 25 ]. The remaining four chickens were assigned to a control group that received a water gavage.…”
Section: Methodsmentioning
confidence: 99%
“…One cause is the difference of pharmacokinetics of MLs in birds and mammals. It has been demonstrated that a fairly low IVM concentration in plasma was obtained when it was orally administrated to laying hens [38, 39]. The other possible reason is the different sensitivity of blood-sucking PRMs and mammals’ mites to MLs.…”
Section: Discussionmentioning
confidence: 99%
“…The residues of ivermectin (IVM) and other macrocyclic lactones preferentially accumulate in the egg yolk following administration to laying hens (Keukens et al, 2000). Accordingly, it was reported that no IVM residues were found in egg white, which contains fat at trace levels, whereas significant IVM residues were measured in egg yolk, which is very rich in lipids, for 5 and 15 days following administration in water for 5 days (Moreno et al, 2015) and single oral administration (Cirak et al, 2018) of IVM, respectively, to laying hens.…”
Section: Discussionmentioning
confidence: 99%
“…SPN (spinosyn A and D) were also analyzed by HPLC with photodiode array (PDA) detector following an SPE procedure similar to the method used to analyze ABM with small modifications, as described below. Previous studies indicated that macrocyclic lactones, including ivermectin, were not detected in egg white (Keukens et al, 2000;Moreno et al, 2015;Cirak et al, 2018) after analysis of egg yolk and white separately. For this reason, only egg yolks were used for HPLC analysis.…”
Section: Analytical Proceduresmentioning
confidence: 97%
See 1 more Smart Citation